Plugged versus Unplugged Activities within Problem-based Learning for Computational Thinking Skills: A Meta-Analytic Review - Suparman; Dadang Juandi; Turmudi; Bambang Avip Priatna Martadiputra (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2025)
The integration of technology in 21st-century education brings considerable advantages, particularly through